Absence of meningeal mast cells in the Mitf mutant mouse - Sabaté San José, Alba; Petersen, Petur Henry (Frontiers in Cellular Neuroscience, 2024)
Mast cells (MCs) are located in the meninges of the central nervous system (CNS), where they play key roles in the immune response. MC-deficient mice are advantageous in delineating the role of MCs in the immune response in vivo. In this study, we illustrate that a mutation in microphthalmia-associated transcription factor (Mitf) affects meningeal MC number in a dosage-dependent manner. C57BL/6J Mitf null mice lack meningeal MCs completely, whereas heterozygous mice have on average 25% fewer MCs. Mitf heterozygous mice might be a valuable tool to study the role of MCs in the meninges.